Satira Politik: Analisis Internet Trolling di Malaysia (Political Satire: Analysis on the Internet Trolling in Malaysia) - Raja Zulkifi, Raja Nurafiqah; Ahmad, Noor Sulastry Yurni; Mohd Sani, Mohd Azizuddin; Muhamad, Haslina (Universiti Kebangsaan Malaysia Press, 2018)
Political satire is a form of political communication composed of various types. Lately, political satire via the Internet is thriving in Malaysia. Internet trolling is available in the form of memes or video and is one of the fascinating medium used in social media as a means of delivering information. This phenomenon has been transmitted in most social media applications. Internet trolling used against political leaders is seen as a type ofpolitical sarcasm. This has become an online phenomenon as part of political news utilised by netizens. This is due to the Internet as a medium of information which is free and easy to access. This article focuses on the participation by the social media users in politicalcommunication via political satire. The design of this study is based on some limited numbers of literature review and theory of social mobilisation and Uses and gratifications theory. The qualitative content analysis is chosen as the research methodology. Facebook is utilised as the medium of analysis through comments selected on Facebook as analytics unit. This study concludes that the phenomenon of political trolling in social media is an indicator that the culture of freedom of speech among the people is progressing. Although the political trolling that has been dispersed through various social media applications is somewhat outrageous, yet these leaders continue to carry out their respective duties regardless of their extreme satire.